2017
DOI: 10.3354/dao03085
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus in bottlenose dolphins Tursiops truncatus

Abstract: Hepatitis E virus (HEV) infects several animal species that act as zoonotic reservoirs for viral transmission. Solid and liquid residues from infected animals could lead to HEV contamination of food and surface waters. Evidence of human HEV infection through ingestion of seafood (shellfish, mussels) has been reported. Dolphins generally feed on fish and squid but are able to adapt to an environment and consume whatever prey is available. Clinical signs of infected dolphins include lethargy, inappetence, behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Gross examinations of internal structures were unremarkable, except for two dolphins (14%) with non-specific lung (Hubbs 0541 Tt) and spleen (IFAW12-198Dd) pathology. One dolphin had signs of hepatitis (IFAW12-201Dd) [48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gross examinations of internal structures were unremarkable, except for two dolphins (14%) with non-specific lung (Hubbs 0541 Tt) and spleen (IFAW12-198Dd) pathology. One dolphin had signs of hepatitis (IFAW12-201Dd) [48].…”
Section: Resultsmentioning
confidence: 99%
“…At necropsy, external and internal examinations were performed and tissue samples were collected for histopathology and infectious disease testing (Morbillivirus, Brucella spp., etc. [48]) where available (S1 Table). Brains from the Massachusetts’ cohort (n = 7 dolphins) were harvested, and a mid-sagittal cut was made to separate each brain into right and left hemispheres.…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, evidence for HEV infection in dolphins, maintained in a National Aquarium in Cuba, was described (Montalvo Villalba et al., ). The authors found HEV‐specific antibodies in 10 of 31 (32%) and HEV‐3‐RNA in 5 of 31 (16%) of the animals.…”
Section: Hev Infection In Animalsmentioning
confidence: 99%
“…Phylogenetic analysis shows that human and swine HEV strains are closely related, with 94%-99% nucleotide sequence identity. Furthermore, seroconversion and HEV-G3b have been recently identified in bottlenose dolphins (Tursiops truncates) in Cuba (13), but the clinical relevance of this infection requires further investigation. Thus, zoonotic HEV-G3 and epidemic HEV-G1 strains seem to co-circulate in Cuba.…”
Section: Hev In Cuba: Epidemiology and Molecular Characterizationmentioning
confidence: 99%
“…HEV-G4 is almost exclusively restricted to Asia (3,4,7). HEV genotypes and reservoirs from nine LAC countries (Argentina, Bolivia, Brazil, Colombia, Costa Rica, Cuba, Mexico, Uruguay, Venezuela) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) are shown in Table 1. Specific clinical manifestations of HEV infection have been tentatively associated with distinct genotypes; for example, HEV-G1 is related to fulminant acute hepatitis in pregnancy, whereas HEV-G3 is associated with chronic liver disease in immunosuppressed patients (2,7).…”
mentioning
confidence: 99%